* (-6)²+(1/3)²÷0,1¹* -5×(-2)⁴+(-3)³+7×4⁰* (1/3-1/6)²×(-36)+1/4×4⁰
* (-6)²+(1/3)²÷0,1¹
* -5×(-2)⁴+(-3)³+7×4⁰
* (1/3-1/6)²×(-36)+1/4×4⁰
Ответ(ы) на вопрос:
1) (-6)²+(1/3)²÷0,1¹= 36 + 1/9 ÷0,1=36+ [latex] \frac{1}{9} [/latex]÷[latex] \frac{1}{10} [/latex] = 36+[latex] \frac{10}{9}[/latex] = 37 [latex] \frac{1}{9} [/latex]
2) -5×(-2)⁴+(-3)³+7×4⁰ = -5×16+(-27)+7×1= -80+(-27)+7= -100
3) (1/3-1/6)²×(-36)+1/4*4⁰ = ([latex]\frac{2}{6} - \frac{1}{6}[/latex])²×(-36)+1/4*1= (-1/6)²×(-36)+1/4= 1/36 × (-36) +1/4= -1+1/4= -3/4
-5х(-2)^4+(-3)^3+7х4^0=-5х16+(-27)+7х1=-80-27+7=-100
(1/3-1/6)^2х(-36)+1/4х4^0=(1/6)^2х(-36)+1/4х1=(1/36)х(-36)+1/4=(-1)+1/4=(-3/4)
(-6)^2+(1/3)^2/0,1^1=36+(1/9:1/10)=36+(1/9х10/1)=36+10/9=324/9+10/9=334/9
Не нашли ответ?
Похожие вопросы